Validation of a dendron concept to tune colloidal stability, MRI relaxivity and bioelimination of functional nanoparticles. Issue 8 (28th February 2015) - Walter, A.; Garofalo, A.; Parat, A.; Jouhannaud, J.; Pourroy, G.; Voirin, E.; Laurent, S.; Bonazza, P.; Taleb, J.; Billotey, C.; Vander Elst, L.; Muller, R. N.; et al.
<x xml:space="preserve">Abstract</x> A dendritic coating induces colloidal stability of nanoparticles through electrostatic and steric interactions.